The Dynamics of Depression in Women in the Antenatal and Postnatal Period - M.V. Nael-Prupes; O.A. Kharkova; A.G. Soloviev; S.S. Nefedova (Клиническая и специальная психология)
More than 10% of women worldwide experience depression during pregnancy and after childbirth. The article presents the results of a study examining the dynamics of depression in women in the antenatal and postnatal periods. To identify the prevalence of depression, the following methods were used: questionnaires and testing. The Beck Depression Scale (BDI) is used to diagnose depression in the antenatal and postnatal period, the Edinburgh Postnatal Depression Scale (EPDS) is used in the postnatal period. The results showed that the prevalence of depression according to BDI at registration for pregnancy was 19,1% (N=162), in the third trimester – 18,3%, 2-6 weeks after delivery – 15,4% (according to EPDS – 21,2%). There was no statistically significant dynamics in depression over time, that is, if a woman is registered for pregnancy with signs of depression, then this condition accompanies her during pregnancy and can lead to postpartum depression. The results of the study substantiate the need to study the psychoemotional state of women at different gestation periods and carry out preventive measures to prevent postpartum depression.